Multivalent display of VP28 on chimeric virus-like particles enhances binding to shrimp target tissues: A novel antiviral strategy against white spot syndrome virus - Somkid Jaranathummakul; Pitchanee Jariyapong; Orawan Thongsum; Supawich Boonkua; Charoonroj Chotwiwatthanakun; Monsicha Somrit; Somluk Asuvapongpatana; Attaboon Wathammawut; Wattana Weerachatyanukul (Veterinary World)
Background and Aim: White spot syndrome virus (WSSV) is a devastating pathogen in shrimp aquaculture, with viral protein 28 (VP28) playing a critical role in host cell attachment and entry. The extracellular domain of VP28 (residues 35–95) is immunogenic and essential for infection; however, its receptor interaction mechanisms remain incompletely elucidated. This study aimed to evaluate the tissue-binding affinity of full-length VP28 and its derived peptides (P1: Residues 35–65; P2: Residues 66–95) as well as a multimeric chimeric virus-like particle (K5-VLP) displaying VP28 on the surface of Macrobrachium rosenbergii nodavirus capsids to enhance host tissue interaction.